Morphological Processes of The Buginese Language in Palu - Yunidar Yunidar; Dian Safitri; Muhammad Ahsan Samad (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This morphology of the Buginese language research aimed to describe the forms of nouns, verbs, and adjectives in the Buginese language in Palu. This research used a descriptive-qualitative method. The data source for this research was the oral text. The techniques of data collection were observation technique, followed by the involved conversation observation technique, the uninvolved conversation observation technique, note-taking and recording techniques. The data were analyzed using matching technique and distributional technique. The results showed that the noun form of the Buginese language consists of basic nouns in concrete form as well as derivative nouns of affixation, reduplication, and compounding noun. Meanwhile, the Buginese verb form consists of basic material and mental verbs, as well as affixation, reduplication, and compounding verbs. In the Buginese language, adjective forms include the basic adjectives of color, size, time, and perception, as well as the derivative adjectives of affixation, reduplication, and compounding.